Responsabilidade socioambiental em empresas familiares brasileiras - Nascimento, Josélia Fernandes do (2020)
The objective of this study consists in verifying whether the Brazilian familiar companies are more prone to be socially and environmentally responsible than those non familiars. To achieve this goal, we made a descriptive research in a quantitative approach, using secondary data. The sample of this study corresponds to open capital institutions listed on the B3 website (Brazil, Bolsa, Balcão), from 2010 to 2018. To measure the Corporative Socioenvironmental Responsibility (CSR) we utilized as proxy a report disclosure of sustainability by the Global Reporting Initiative (GRI) pattern, or the participation of the company in the Company Sustainability Index (CSI). The information about the adoption of the GRI pattern were collected on the sustainability reports disclosed on the Companies websites and the participation in the CSI was observed on the website of the B3. The variable that represents the classification of the companies as familiar was estimated by the involvement of the family members in the property, and by the control and management of the organization, simultaneously. To do this classification, it was consulted the Reference Formularies available on the website of the B3. In relation to the control variables that compose the model, the collect of data was made through the data base of Thomson Reuters Eikon. To analyze the data, it was estimated a data model on a panel with binary dependent variable, utilizing a logistic regression, in other words, logit panel. The results found out that there exists an inverse relation between the CSR and the familiar company, in other terms, the fact that the company to be a familiar one decreases the chances of presenting socioenvironmental responsibility in comparison with a nonfamiliar establishment. Besides, in terms of proportional ratio chances, we realized that if the company is familiar, the probability of presenting a good socioenvironmental behavior diminish in a 50% rate. This way, we can infer that, if the Brazilian familiar companies of open capital present lower performance of CSR than those non-familiar, likewise, they are less worried in legitimate their actions, contrasting to what propose the Legitimacy Theory.